Penentuan Persentase Pajak Progresif Ditinjau Berdasarkan Asas Keadilan dan Kemanusiaan - Mohammad Syauqi Pakaya; Nirwan Junus; Mellisa Towadi (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2023)
Departing from legal issues regarding progressive taxes with different percentages from non-progressive taxes, this study aims to find out whether the determination of progressive taxes is in accordance with the principles of justice and humanity or not. Because as we know, this progressive tax has a larger percentage than non-progressive taxes. In addition, the purpose of this study is also to find out how the government can determine which taxpayers are charged as progressive taxpayers, of course there is a separate classification so that the taxation government classifies them as progressive taxpayers. This research is a type of normative research with a statute approach, historical approach, and analytical approach. The source of data from this study is secondary legal material consisting of primary, secondary and tertiary legal materials. Data collection techniques are document and literature studies, then for data analysis is a descriptive qualitative method. Determination of the percentage of progressive tax in this case is in accordance with the provisions of the law in force and by taking into account or in accordance with the principles of justice and humanity, besides that the taxation government in determining the taxpayer as a progressive taxpayer has its own provisions.